YB-1-based oncolytic virotherapy in combination with CD47 blockade enhances phagocytosis of pediatric sarcoma cells - von Ofen, Anna Josefine; Thiel, Uwe; Eck, Jennifer; Gassmann, Hendrik; Thiede, Melanie; Hauer, Julia; Holm, Per Sonne; Schober, Sebastian J. (Frontiers in Oncology, 2024)
Oncolytic viruses (OVs) selectively replicate in tumor cells resulting in lysis, spreading of new infectious units and induction of antitumor immune responses through abrogating an immunosuppressive tumor microenvironment (TME). Due to their mode of action, OVs are ideal combination partners with targeted immunotherapies. One highly attractive combination is the inhibition of the ‘don’t-eat-me’-signal CD47, which is known to increase the phagocytic potential of tumor-associated macrophages. In this work, we analyzed the combination approach consisting of the YB-1-based oncolytic adenovirus XVir-N-31 (XVir) and the CD47 inhibitor (CD47i) B6.H12.2 concerning its phagocytic potential. We investigate phagocytosis of XVir-, adenovirus wildtype (AdWT)-, and non-infected established pediatric sarcoma cell lines by different monocytic cells. Phagocytes (immature dendritic cells and macrophages) were derived from THP-1 cells and healthy human donors. Phagocytosis of tumor cells was assessed via FACS analysis in the presence and absence of CD47i. Additional characterization of T cell-stimulatory surface receptors as well as chemo-/cytokine analyses were performed. Furthermore, tumor cells were infected and studied for the surface expression of the ‘eat-me’-signal calreticulin (CALR) and the ‘don’t-eat-me’-signal CD47. We herein demonstrate that (1) XVir-infected tumor cells upregulate both CALR and CD47. XVir induces higher upregulation of CD47 than AdWT. (2) XVir-infection enhances phagocytosis in general and (3) the combination of XVir and CD47i compared to controls showed by far superior enhancement of phagocytosis, tumor cell killing and innate immune activation. In conclusion, the combination of CD47i and XVir causes a significant increase in phagocytosis exceeding the monotherapies considerably accompanied by upregulation of T cell-stimulatory receptor expression and inflammatory chemo/-cytokine secretion.